New locality records for Steinernema and Heterorhabditis (Nematoda: Rhabditida: Steinernematidae, Heterorhabditidae) fauna of Ukraine - Kovtun , A. (Quarantine and plant protection, 2023)
Goal. Of this study is to present new locality records (from agricultural ecosystems) for Steinernema and Heterorhabditis (Nematoda: Rhabditida: Steinernematidae, Heterorhabditidae) fauna of Ukraine. Methods. The object of our research were entomopathogenic nematodes collected from different localities of Ukraine between 2016 and 2021. We used stereoscopic microscope MBS-9, light microscope Carl Zeiss Primo Star 100x—1000x and specialized keys for entomopathogenic nematodes identification. Results. We analyzed 312 samples for entomopathogenic nematodes (Steinernematidae, Heterorhabditidae). Entomopathogenic nematodes were isolated from Zhytomyr region, Chernihiv region and Kyiv region. Entomopathogenic nematodes from Zhytomyr region and Chernihiv region is a new record for Ukraine. EPN-positive soil samples with Steinernema spp. were noticeably pre-dominating over the Heterorhabditis spp. (ratio 1.5 to 1). Three species of entomopathogenic nematodes (S. carpocapsae, Steinernema sp. «glaseri»-group and H. bacteriophora), have been described. The information on the specimens location and brief notes on the habitats is provided. In present study, we examined differences in the morphological and morphometric characters between two EPN species from different regions/zones of Ukraine. Conclusions. We found new locality records for two entomopathogenic nematodes species: S. сarpocapsae and H. bacteriophora reported from Zhytomyr region and Chernihiv region of Ukraine for the first time. Further studies aiming to improve the knowledge on entomopathogenic nematodes (Steinernema and Heterorhabditis) fauna should focus on collecting in little-known areas and some specific habitats of Ukraine.